Antimicrobial Activity of Selected Banana Cultivars Against Important Human Pathogens, Including Candida Biofilm - Ramin Saleh Jouneghani; Ana Hortência Fonsêca Castro; Sujogya Kumar Panda; Rony Swennen; Walter Luyten (Foods, 2020)
Ten banana (Musa spp.) cultivars were studied for their antimicrobial properties. Three plant parts (corm, pseudostem and leaves) were collected separately and extracted with different solvents, viz., hexane, acetone, ethanol and water. The 50% inhibitory concentration (IC50) was evaluated using a broth microdilution assay. Eight human bacterial and one fungal pathogen were tested. Acetone and ethanol extract(s) often exhibited significant antimicrobial activity, while hexane extracts were less active. Aqueous extracts often showed microbial growth, possibly by endophytes. Leaf extracts were most active, followed by pseudostem, and corm was least active. All the tested banana cultivars were found to contain antimicrobials, as demonstrated by inhibition of selected human pathogens. However, cultivars such as Dole, Saba, Fougamou, Namwah Khom, Pelipita and Mbwazirume showed a broad-spectrum activity, inhibiting all tested pathogens. Other cultivars such as Petit Naine and Kluai Tiparot showed a narrow-spectrum activity, including antibiofilm activity against Candida albicans. Our results support the use of different parts of banana plants in traditional human medicine for infections, including diarrhea and dysentery, and some sexually transmitted diseases, as well as for packaging spoilable materials like food.